Creator Culture : An Introduction to Global Social Media Entertainment - Baym, Nancy K.; Craig, David Randolph; Cunningham, Stuart (Book collections on Project MUSE., 2021)
"Creator Culture introduces readers to "ways of seeing" social media entertainment from perspectives that critically assess claims for its relation to, yet differentiation from, well-established media forms and institutions within scope for cultural and media studies, including emerging platform and social media studies"--